Ø§Ù„Ø·Ù„Ø¨Ø© Ø§Ù„ÙØµØØ§Ø¡ ÙÙŠ Ø§Ù„ÙƒÙ„Ø§Ù… Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ù…Ù†Ø¸ÙˆØ± Ø¹Ù„Ù… Ø§Ù„Ù…Ø¹Ø§Ù†ÙŠ :Ø¯Ø±Ø§Ø³Ø© ÙˆØµÙÙŠØ© ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø¹Ù„ÙˆÙ… Ø¨Ø§Ù†ÙŠÙˆØ£Ù†ÙŠØ§Ø± Ø§Ù„Ø§Ø³Ù„Ø§Ù…ÙŠ Ø¨Ø§Ù…ÙŠÙƒØ§Ø³Ø§Ù† - Hadi, Nurul (OKARA: Jurnal Bahasa dan Sastra, 2019)
The most representative indicator of the success of Arabic learning process is the fluency of the students’ speaking by using Arabic. This study aims to determine whether there are students who are fluent in spoken Arabic, to identify the students’ characteristics who are categorically fluent in spoken Arabic, to identify how students gain fluency in spoken Arabic based on Ma’ani science perspective. This is a descriptive qualitative study, the data collected by using interviews, questionnaires, and observation. The data sources were the preachers/teachers and the students who were active and had been active in the Arabic Language Center of Darul Ulum Islamic Boarding School of Banyuanyar. The results of this study revealed: First, students who are fluent in spoken Arabic were classified as fluent after studying Arabic for four months at the Arabic Language Center. Second, there are four indicators of students to be classified as fluent Arabic speakers, the first and the most representative indicator is the proficiency of students in Arabic debate contest in various themes, the second is students’ ability to converse using Arabic in many different situations, the third is the ability to talk using the original Arabic, and the fourth is the students’ ability in a Arabic speech. The way the students gain fluency in spoken Arabic is dependent on the personality of each student. The diligent students tend to have high spirit in practicing conversational Arabic, acquiring and learning Arabic, and also supported by strong intelligence, then they will acquire fluency in speaking Arabic.